Identification of an imidazopyridine scaffold to generate potent and selective TYK2 inhibitors that demonstrate activity in an in vivo psoriasis model. Issue 18 (15th September 2017) - Liang, Jun; Van Abbema, Anne; Balazs, Mercedesz; Barrett, Kathy; Berezhkovsky, Leo; Blair, Wade S.; Chang, Christine; Delarosa, Donnie; DeVoss, Jason; Driscoll, Jim; Eigenbrot, Charles; Goodacre, Simon; et al.
Graphical abstract: Abstract: Herein we report identification of an imidazopyridine class of potent and selective TYK2 inhibitors, exemplified by prototype6, through constraint of the rotatable amide bond connecting the pyridine and aryl rings of compound1 . Further optimization led to generation of compound30 that potently inhibits the TYK2 enzyme and the IL-23 pathway in cells, exhibits selectivity against cellular JAK2 activity, and has good pharmacokinetic properties. In mice, compound30 demonstrated dose-dependent reduction of IL-17 production in a PK/PD model as well as in an imiquimod-induced psoriasis model. In this efficacy model, the IL-17 decrease was accompanied by a reduction of ear thickness indicating the potential of TYK2 inhibition as a therapeutic approach for psoriasis patients.